Relationship between Instructional Leadership and Implementation of Competency-Based Curriculum in Early Years Education in Nairobi City County, Kenya - Roselynn Awili; Nyakwara Begi (Randwick International of Education and Linguistics Science Journal, 2021)
Globally, learning institutions at primary school level experience a gap in instructional leadership that fosters curriculum implementation. Research has established that those instructional leaders (heads of schools) determine the impact that teaching and learning processes in school has on learners’ academic performance. This study was designed to establish the extent of implementation of Competency-Based Curriculum in early years education in public and private schools. The study was also to determine the relationship between instructional leadership and implementation of Competency-Based Curriculum (CBC) in early years education in Kenya. The study was guided by Michael Fullan’s Theory of Change. The dependent variable was implementation of Competency-Based Curriculum in early years education while the independent variable was instructional leadership. E-questionnaires and interview schedules were used to collect data which was analyzed using qualitative and quantitative methods. The results showed there was no difference in the implementation of curriculum between private and public primary schools. The relationship between instructional leadership and implementation of competency-based curriculum was significant at 0.05. The results also indicated that most head teachers focused more on administrative roles than activities that support curriculum implementation. It was therefore recommended that for effective curriculum implementation in early years education, head teachers needed to be intentionally trained on how to support teachers and learners in the related processes